Cost, revenue and profit efficiency in Islamic vs. conventional banks: empirical evidence using Data Envelopment Analysis (DEA) - Kamarudin, Fakarudin; Yahya, Mohamed Hisham (Universiti Putra Malaysia Press, 2013)
The objective of this study is to compare the cost, revenue and profit efficiency of Islamic and conventional banks in Malaysia over the period 2006 to 2009. To represent the Malaysian Islamic and conventional banking sector, a sample of 39 banks were selected to participate in the study. The level of efficiencies was measured using the Data Envelopment Analysis (DEA) method, which applied the intermediation approach. The result shows that the levels of cost and profit efficiency for Malaysian Islamic banks are lower compared to the Malaysian conventional banks. The difference levels between cost and profit efficiency in the Malaysian banking sector are not influenced by revenue efficiency but, rather are subject to influence by internal and external factors.